Madeline's rescue - Bemelmans, Ludwig, 1898-1962. (New York : Viking, 1953)
A hound rescues a schoolgirl from the Seine, becomes a beloved school pet, is chased away by the trustees, and returns with a surprise.
Caldecott Medal/Honor
School Library Journal
Wilson's Children
Book Links (A.L.A.), July 2009
Booklist, November 2008
Bulletin (Center for Children's books), December 2008
Keywords: Dogs -- Fiction; Madeline (Fictitious character) -- Fiction; Stories in rhyme; Dogs -- Fiction; Madeline (Fictional character) -- Fiction; Stories in rhyme; Paris (France) -- Fiction; Paris (France) -- Fiction